Effect of substrate temperature on the structural and electrical properties of spray deposited lead sulfide thin films. (2016) - Veena, E.; Bangera, Kasturi V.; Shivakumar, G.K.
Abstract: Lead sulfide (PbS) thin films were prepared by chemical spray pyrolysis method using lead acetate and thiourea as precursors of Pb +2 and S -2 ions. X-ray diffraction (XRD) technique, scanning electron microscope (SEM) and EDAX analysis were used for structural, morphological and compositional characterization. XRD analysis shows that the films are cubic in nature with a preferred orientation along (2 0 0). EDAX analysis shows that films deposited at 150°C are sulfur rich. An increase in the substrate temperature results in a decrease in the sulfur content of the prepared film. It has been observed that thin films deposited at or above 225°C are smooth & uniform morphologically. Beyond a substrate temperature of 275°C, the films become discontinuous and non-uniform. However, the films are sulfur rich, even at 275°C. Electrical conductivity of prepared thin films have been measured using silver contacts in coplanar geometry. Films are n - type as confirmed by hot probe technique. The electrical conductivity at room temperature (25°C) was in the order of 10 -4 Ω -1 cm -1 and was found to increase with increase in temperature showing the semiconducting nature of the films with the band gap of 0.39 eV.